Public Health Policy Actions to Address Health Issues Associated with Drought in a Changing Climate. Issue 4 (2020) - Ganesh, Chandra; Schmeltz, Michael; Smith, Jason; Lookadoo, Rachel E.; Bell, Jesse E.
Abstract : Over the last century, droughts have caused more deaths internationally than any other weather- or climate-related disaster. Like other natural disasters, droughts cause significant changes in the environment that can lead to negative health outcomes. As droughts are becoming more frequent and intense with climate change, public health systems need to address impacts associated with these events. Partnering with federal and local entities, we evaluated the state of knowledge of drought and health in the United States through a National Drought and Public Health Summit and a series of subsequent regional workshops. The intended outcome was to develop public health strategies for implementing activities to better support and prepare public health systems for future droughts. The information gathered from this work identified multiple policy and law options to address the public health issues associated with drought. These policy recommendations include the use of public health emergency declarations for drought events, increased usage of preparedness evaluations for drought emergencies, and engagement of drought and climate experts in state and local risk assessments. As drought events are projected to increase in frequency and magnitude with climate change, taking policy action now will help decrease the health impacts of drought and save lives.